Population genetics of structural variation - Conrad, Don (Henry Stewart Talks, 2009)
Importance of ascertainment, Mutation processes, rates and mutation rate modifiers, Interplay between structural variation and recombination and gene conversion, Distribution of structural variants within and between human populations, Shared patterns of SV polymorphism among species, Functional constraint on CNVs, Evidence for positive selection on CNVs
Archived at 2021/02/25